Enhancement of Succinic Acid Production by Actinobacillus succinogenes in an Electro-Bioreactor - Julian Tix; Leon Gotthardt; Joshua Bode; Burak Karabacak; Janne Nordmann; Jan-Niklas Hengsbach; Roland Ulber; Nils Tippkötter (Fermentation, 2024)
This work examines the electrochemically enhanced production of succinic acid using the bacterium Actinobacillus succinogenes. The principal objective is to enhance the metabolic potential of glucose and CO2 utilization via the C4 pathway in order to synthesize succinic acid. We report on the development of an electro-bioreactor system to increase succinic acid production in a power-2-X approach. The use of activated carbon fibers as electrode surfaces and contact areas allows A. succinogenes to self-initiate biofilm formation. The integration of an electrical potential into the system shifts the redox balance from NAD+ to NADH, increasing the efficiency of metabolic processes. Mediators such as neutral red facilitate electron transfer within the system and optimize the redox reactions that are crucial for increased succinic acid production. Furthermore, the role of carbon nanotubes (CNTs) in electron transfer was investigated. The electro-bioreactor system developed here was operated in batch mode for 48 h and showed improvements in succinic acid yield and concentration. In particular, a run with 100 µM neutral red and a voltage of −600 mV achieved a yield of 0.7 gsuccinate·gglucose−1. In the absence of neutral red, a higher yield of 0.72 gsuccinate·gglucose−1 was achieved, which represents an increase of 14% compared to the control. When a potential of −600 mV was used in conjunction with 500 µg∙L−1 CNTs, a 21% increase in succinate concentration was observed after 48 h. An increase of 33% was achieved in the same batch by increasing the stirring speed. These results underscore the potential of the electro-bioreactor system to markedly enhance succinic acid production.